Suppose you are having a birthday party at the local bowling alley. You’re trying to figure out how many people you can afford to invite. 1) The number of guests you can invite to the party varies inversely with the price per bowler at the alley. Explain what this means.

2) How much total money are you willing to spend to host this bowling party?
Willing to spend: $ _

3) Set up an equation that shows the inverse relationship between the number of guests at your party and the price per bowler. Your answer for part 2 should be part of your equation.

y=


4) Research two local bowling alleys. Record the price per bowler at each of these two alleys.
Bowling Alley #1 $ /bowler
Bowling Alley #2 $ /bowler

5) Calculate how many guests you will be able to invite to your party at each of the bowling alleys.
Alley Total
Bowling Alley #1
Bowling Alley #2


Which alley would you choose for your party? Why?

Answers

Answer 1
Answer: 1) The number of guests you can invite to the party varies inversely with the price per bowler at the alley. This means that the higher the number of guests you invite, the lower the price per bowler and vice versa.

2) The amount of money you are willing to spend will be according to your discretion. Let us assume that the money you are willing to spend is represented by M.

3) y = M/x
where: M is the amount of money you are willing to spend
x is the number of guests your are inviting
y is the price per bowler





Related Questions

Jessica cannot remember the correct order of the five digits in her ID number. She does remember that the ID number contains the digits 9, 0, 3, 1, 5. What is the probability that the first four digits of Jessica's ID number will all be odd numbers?
the Revenue for the week is $2000, and labor cost consists of two workers earning $8 per hour who work 40 hours each, what is labor cost as a percentage of Revenue?
43.7 is what percent of 9,2
Solve the equation X^2 +10x+24=0
Solve the equation: x^2 - 6x = 7 A. x = 7 , 1 B. x = -7 , 1 C. x = 7 , -1

Can anyone help me?

Answers

y = √(-x + 3)
Domain: x ≤ 3

y = √(3x)
Domain: x ≥ 0

X+7x+4-5x+8=12 please help meeee!

Answers

Answer:

THERE

Step-by-step explanation:

To solve the equation x + 7x + 4 - 5x + 8 = 12, we can combine like terms on both sides of the equation:

Starting with the left side of the equation:

x + 7x - 5x + 4 + 8 = 12

Combining like terms:

3x + 12 = 12

Next, we can isolate the variable by subtracting 12 from both sides of the equation:

3x + 12 - 12 = 12 - 12

Simplifying:

3x = 0

To solve for x, we divide both sides of the equation by 3:

(3x)/3 = 0/3

Simplifying further:

x = 0

Therefore, the solution to the equation x + 7x + 4 - 5x + 8 = 12 is x = 0.

What is the additive inverse of the polynomial -9x2+6x2y-5x3

Answers

The additive inverse of the equation is 9x2 - 6x2y + 5x3.

Simplify –2x3y × xy 2. A. –12x4y3

B. –2x3y4

C. –2x4y3

D. –3x4y3

Answers

-2x^3y\cdot xy^2=-2x^(3+1)y^(1+2)=-2x^4y^3

Used:

a^n\cdot a^m=a^(n+m)

Answer: C. –2x^4y^3

Describe this pattern. Then see if you can think of another Pythagorean triple that doesn't follow the pattern you just described and that can't be generated using the identity (x2 − 1)2 + (2x)2 = (x2 + 1)2. Explain your findings. x-value Pythagorean Triple 7 (14,48,50) 8 (16,63,65) 9 (18,80,82) 10 (20,99,101)

Answers

Answer:

See explanation

Step-by-step explanation:

A Pythagorean triple is a set of 3 positive integer numbers, a, b, and c which satisfies the Pythagorean theorem: c^2=a^2+b^2

Given the identity: (x^2 - 1)^2 + (2x)^2 = (x^2 + 1)^2.

We verify that the numbers given table are Pythagorean triples.

14^2+48^2=2500=50^2\n16^2+63^2=4225=65^2\n18^2+80^2=6724=82^2\n20^2+99^2=10201=101^2

Next, we examine the pattern:

\left|\begin{array}{c|c|c|c|c}x-value&x^2-1&2x&x^2 + 1&$Triple\n--&--&--&--&----\n7&48&14&50&(14,48,50)\n8&63&16&65&(16,63,65)\n9&80&18&82&(18,80,82)\n10&99&20&101&(20,99,101)\end{array}\right|

From the pattern, our first number is 2x, the second number is x² - 1, and the third number(hypotenuse) is x² + 1

Next, we show that  (x² - 1)² + (2x)² = (x² + 1)² is an identity

LHS: (x^2 - 1)^2 + (2x)^2 \n= (x^2-1)(x^2-1)+2x^2\n=x^4-2x^2+1+4x^2\n=x^4+2x^2+1

RHS: (x^2+1)^2\n= (x^2+1) (x^2+1)\n=x^4+2x^2+1 

Since Left Hand Side=Right hand Side. For all x, the equation is always true.

Therefore, the pattern is true for any Pythagorean triple.

Find the equation of this line

Answers

Answer:

y = 2x + 4

Step-by-step explanation:

The slope is 2/1 (or just 2) and the 4 is the y-intercept

Answer:

y = 2x + 4

Step-by-step explanation:

B is the y-intercept. The y-intercept of this graph is (0,4).

Rise over run, count up and to the right giving you 2/1 which equals 2.

Thus, y = 2x + 4